1989
DOI: 10.1037/0735-7044.103.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Brain transplants enhance rather than reduce the impairment of spatial memory and olfaction in bulbectomized rats.

Abstract: The possibility to compensate the loss of olfactory and non-olfactory functions due to removal of the olfactory bulb by embryonal brain grafts was investigated in adult rats. Spatial working memory was examined in an 8-arm radial water maze task 6 weeks after bulbectomy. During 15 daily trials, performance gradually improved in bulbectomized controls (n = 10) and in rats with olfactory bulb transplants (n = 9), but did not attain that of intact controls (n = 10). No improvement was observed in the rats with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 30 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…The triple transgenic mouse model of AD (3xTg-AD) generated by LaFerla and colleagues [ 25 ] harbors three transgenes of Presenilin 1 (PS1, M146V), tau (P301L) and Amyloid precursor protein (APP, SWE) and manifests the two major pathological features seen in AD patients, namely A β plaques and neurofibrillary tangles. Extracellular amyloid plaques are observed in 3xTg-AD animals in the frontal cortex at six months of age and in the hippocampus by 12 months followed by neurofibrillary tangles, leading to a memory deficit measurable in the Morris water maze (MWM) test [ 1 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The triple transgenic mouse model of AD (3xTg-AD) generated by LaFerla and colleagues [ 25 ] harbors three transgenes of Presenilin 1 (PS1, M146V), tau (P301L) and Amyloid precursor protein (APP, SWE) and manifests the two major pathological features seen in AD patients, namely A β plaques and neurofibrillary tangles. Extracellular amyloid plaques are observed in 3xTg-AD animals in the frontal cortex at six months of age and in the hippocampus by 12 months followed by neurofibrillary tangles, leading to a memory deficit measurable in the Morris water maze (MWM) test [ 1 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…This recovery did not occur in rats that received fetal mesencephalic tissue grafts. Amemori et al (1989) and Choulli et al hypothesized that the reinnervation of the host brain by the transplanted tissue disrupted processes within the host brain that occurred in the nontransplanted rats and were beneficial to behavioral recovery. These processes could include either unmasking of previously silent circuits or anatomical reorganization such as takes place during reactive synaptogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the experiment by Dalrymple-Alford et al (1988), at least four other studies have noted transplant–induced behavioral impairment, and all have observed that this impairment was relative to rats with lesions that showed some amount of time-related behavioral recovery. Amemori et al (1989) observed that bulbectomized rats exhibit deficits in spatial learning tasks. Some recovery occurred in these animals with time, but this recovery was not evident in bulbectomized rats that received fetal transplants.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the adverse effect of OB and corpus striatum transplants was probably due to their poor connectivity with the host brain, which prevented the regenerating olfactory axons from reaching higher olfactory centers. In the next study of Amemori et al (1989) the possibility to compensate the loss of olfactory and non-olfactory functions, induced by the removal of the OB, by embryonal OB grafts was investigated in adult rats. Spatial working memory of the animals was examined in the radial water maze task 6 weeks after bulbectomy/transplantation.…”
Section: Homotopic Olfactory Bulb Transplantatioňmentioning
confidence: 99%